2015
DOI: 10.1177/1073191115587551
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Cross-Validation of Cutoff Scores for Patients With Schizophrenia Spectrum Disorders on WAIS-IV Digit Span–Based Performance Validity Measures

Abstract: Two studies were conducted to identify and cross-validate cutoff scores on the Wechsler Adult Intelligence Scale-Fourth Edition Digit Span-based embedded performance validity (PV) measures for individuals with schizophrenia spectrum disorders. In Study 1, normative scores were identified on Digit Span-embedded PV measures among a sample of patients (n = 84) with schizophrenia spectrum diagnoses who had no known incentive to perform poorly and who put forth valid effort on external PV tests. Previously identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…First, in the combined no/mixed and negative incentive subsamples of the referral center, psychotic patients had higher error scores on the forced-choice PVT than non-psychotic patients. This finding is congruent with Hunt, Root, and Bascetta (2014), who found elevated error scores on PVTs in patients with schizophrenia and schizoaffective disorder (see also Glassmire, Toofanian Ross, Kinney, & Nitch, 2016;Peters, Jelicic, Moritz, & Jelinek, 2013), and also with studies that demonstrated a relative impairment of patients with schizophrenia in emotional recognition in facial expressions (for an overview, see Edwards, Jackson, & Pattison, 2002). Our first finding is substantiated by our second: referral center patients with an incentive to deny their impairment, most of whom (79%) were classified as having a psychotic disorder, made significantly more errors than healthy controls on a PVT, whereas they performed at a similar level as native Dutch, chronic psychotic patients.…”
Section: Discussionsupporting
confidence: 85%
“…First, in the combined no/mixed and negative incentive subsamples of the referral center, psychotic patients had higher error scores on the forced-choice PVT than non-psychotic patients. This finding is congruent with Hunt, Root, and Bascetta (2014), who found elevated error scores on PVTs in patients with schizophrenia and schizoaffective disorder (see also Glassmire, Toofanian Ross, Kinney, & Nitch, 2016;Peters, Jelicic, Moritz, & Jelinek, 2013), and also with studies that demonstrated a relative impairment of patients with schizophrenia in emotional recognition in facial expressions (for an overview, see Edwards, Jackson, & Pattison, 2002). Our first finding is substantiated by our second: referral center patients with an incentive to deny their impairment, most of whom (79%) were classified as having a psychotic disorder, made significantly more errors than healthy controls on a PVT, whereas they performed at a similar level as native Dutch, chronic psychotic patients.…”
Section: Discussionsupporting
confidence: 85%
“…The digit span test is one of 15 subtests of the Wechsler Adult Intelligence Scale (WAIS), which was developed as a measure of attention, concentration, and memory ( Glassmire et al, 2016 ). On this test, progressive sequences of numerals were presented orally, whereby the examinee reproduced them immediately after the presentation.…”
Section: Methodsmentioning
confidence: 99%
“…First, patients were excluded if their performance on an at least one PVT was indicative of inadequate effort ( N = 5) 1 . Using cutoff scores identified by Glassmire, Toofanian Ross, Kinney, and Nitch (2016) for use of the Reliable Digit Span as an EVI in samples with SSDs, two additional patients were removed for earning a score of ≤4 on the Reliable Digit Span. In addition, data were included only for cases in which the test administration was explicitly characterized as valid in the report ( N = 140), and an additional 20 records were excluded because the clinician did not explicitly opine that the patient was not feigning or malingering ( N = 120).…”
Section: Methodsmentioning
confidence: 99%